Mechanical and propulsive efficiency of swimmers in different zones of energy supply - Kolmogorov, S.; Vorontsov, A. R.; Rumyantseva, O. A.; Kochergin, A. B. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The goal of the research was experimental studying of regularities for metabolic energy transformation into velocity of human`s swimming by sports strokes in different zones of energy supply on the basis of the mathematical model of this process: v0 = Pai*eg*ep / Fr(f.d.), in which v0 is mean swimming velocity at the competitive or training distance {m/s}; Pai is power of active energetic metabolism W; eg is dimensionless coefficient of mechanical efficiency; ep is dimensionless coefficient of propulsive efficiency; Fr(f.d.) is frontal component of active drag force N (Kolmogorov, 1997)